2013
DOI: 10.1021/om400611t
|View full text |Cite
|
Sign up to set email alerts
|

Rational Synthesis of Heteroleptic Tris(chelate) Ruthenium Complexes [RuII(2-Ph-2′-Py)(LL)(L′L′)]PF6 by Selective Substitution of the Ligand Trans to the Ruthenated Phenyl Ring

Abstract: [Ru(N∧N)(MeCN)2(2-Ph-2′-Py)]PF6 (2-Ph-2′-Py = ortho-metalated 2-phenylpyridine, N∧N = phenanthroline, 2,2′-bipyridine), in which one of the nitrogens of the N∧N ligand is bound to Ru trans to the phenyl unit of 2-PhPy, were slowly isomerized (2 days) in refluxing 1,1-dichloroethane/MeCN (9/1) or more rapidly (although with a reduced yield) in the presence of UV light, to afford compounds in which the same N atom was bound to Ru trans to the pyridine of 2-PhPy; these new compounds, in opposition to their well-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The synthesized cycloruthenated complexes produced significant cytotoxic effects in mammalian tumor cells that were similar to cisplatin and were less likely to produce neurotoxicity compared to cisplatin. 226,227 Fetzer et al . synthesized a series of cycloruthenated compounds with N-C-N and N-N-C pincer derivatives (Fig.…”
Section: Ruthenium(ii) Polypyridyl Complexesmentioning
confidence: 99%
“…The synthesized cycloruthenated complexes produced significant cytotoxic effects in mammalian tumor cells that were similar to cisplatin and were less likely to produce neurotoxicity compared to cisplatin. 226,227 Fetzer et al . synthesized a series of cycloruthenated compounds with N-C-N and N-N-C pincer derivatives (Fig.…”
Section: Ruthenium(ii) Polypyridyl Complexesmentioning
confidence: 99%
“…The four cycloruthenated complexes [ 2 ]PF 6 –[ 5 ]PF 6 were prepared as shown in Scheme , following the synthetic route established by the Pfeffer group . The dimer [(η 6 ‐C 6 H 6 )RuCl(μ‐Cl)] 2 was heated in CH 3 CN at 45 °C together with NaOH, KPF 6 , and Hphpy to yield the cycloruthenated complex [Ru(phpy)(CH 3 CN) 4 ]PF 6 .…”
Section: Resultsmentioning
confidence: 99%
“…However, Pfeffer et al. recently showed that this structural assignment might not be correct . CH 3 CN is a very good ligand for ruthenium(II), and in order to turn it into a good leaving group the complex must first isomerize (either thermally or photochemically) so that one CH 3 CN ligand becomes trans to the carbon ligand, which is a very reactive position due to the trans effect of the C donor atom .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations